BETERNAK KELINCI MENGGUNAKAN TEKNIK SWAPTER - Cahyono, Hendra; Susilo, Budi; Wijayanto, Terry Okta (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The humanâs need of protein from meat is very high. However, in the market recently found unhealthy meat such as beef and chicken. Thatâs why; itâs very natural if the society tries to find the other source of meat, for example rabbitsâ meat. Rabbitsâ livestock now days become a rare activity in our society, in the other hand the global market of rabbitsâ meat become a potential business. The expectations from rabbitsâ livestock are able to minimize the finance and maximize the profit, create the profitable and inovative job opportunities. However, those still give the efective time. To realize this, the rabbitsâ livestock business is conducted with swapter technique. Swapter technique is an effort conducted to create or to make its livestock woof. Water spinach is given as the staple food and also the rice powder and curcumma as the medicine or appetite supplement.Â